Evaluation of the Effectiveness of Human Resources Management Improving the Quality of School Education - Indra Wahyudi Z; Inom Nasution; Lia Sumayyah; Salwa Salsabila; Melin Andila; Aisyah Oktavian; Mustofa Siregar (Education Achievement: Journal of Science and Research, 2024)
This article aims to evaluate the effectiveness of human resource management (HR) in improving the quality of education in schools. Through a comprehensive approach, this article will analyze various aspects of human resource management in schools, including planning, development and evaluation of the performance of teaching and education staff. Furthermore, the impact of HRM on improving the quality of learning processes and outcomes in schools will be studied in depth. The resulting findings and recommendations are expected to provide insight for stakeholders in efforts to improve the effectiveness of HRM and the quality of education in schools.